Induction potential of clavulanic acid toward L1 and L2 β-lactamases of Stenotrophomonas maltophilia - C.-W. Lin; R.-M. Hu; S.-C. Huang; Y.-J. Hsiao; T.-C. Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Identification and expression characterization of pepsinogen A in orange‐spotted grouper, Epinephelus coioides - S. Z. Feng; W. S. Li; H. R. Lin (Journal of Fish Biology, 2008)
To understand the molecular mechanisms associated with digestive physiology of the stomach of orange‐spotted grouper Epinephelus coioides , a cDNA library was constructed and 331 expressed sequence tags (EST) were generated and annotated. About 37·17% of 226 identified ESTs were possibly related to digestive enzymes. Two type‐A pepsinogens differing in putative isoelectric point were identified and characterized for the first time in E. coioides . The complete cDNAs were 1312 and 1314 bp in length, and the deduced polypeptide sequences comprised 376 and 377 amino acids, respectively. Both genes consisted of eight introns of various lengths. Alignment and a phylogenetic tree based on the amino acid sequences of pepsins indicated that pepsin A1 and A2 could be classified into two different subtypes. Northern blot hybridization showed that there were two forms of transcripts for pepsinogen A1 and three for pepsinogen A2. Reverse transcription‐PCR (RT‐PCR) followed by Southern blot analysis revealed that two type‐A pepsinogen mRNAs were present in the adult stomach tissue, and pepsinogen A2 was also detectable in the mid‐intestine. Furthermore, pepsinogen A1 transcript was first detected at 29 days post‐hatching, while pepsinogen A2 was continuously expressed through hatching to adult fish. These results imply that transcriptional regulation and physiological function of the two type‐A pepsinogens may be different.

Cigarette smoking and prostate cancer-specific mortality following diagnosis in middle-aged men - Zhihong Gong; Ilir Agalliu; Daniel W. Lin; Janet L. Stanford; Alan R. Kristal (Cancer Causes & Control, 2008)